UPAYA MENINGKATKAN KETERAMPILAN MOTORIK HALUS MELALUI KEGIATAN MERONCE MENGGUNAKAN BAHAN CLAY PADA KELOMPOK USIA 4-5 TAHUN DI RA ROFA KECAMATAN CIAWI KABUPATEN BOGOR - Eva Farhanah Hasyim; Elnawati Elnawati; Indra Zultiar (CV. Adiba Aisha Amira, 2025)
This study aims to analyze the impact of threading activities using clay materials on the development of fine motor skills in children aged 4-5 years at RA ROFA, Ciawi District, Bogor Regency. Fine motor skills are an important aspect of child development, influencing their ability to perform daily activities. The method used in this research is Classroom Action Research (CAR), conducted in two cycles, involving 16 children as research subjects, consisting of 13 boys and 3 girls. The results of the study indicate that threading activities with clay media can significantly improve children's fine motor skills. Before the implementation of the activities, the children's fine motor skills were in the underdeveloped category, with an average score of 50.32%. After the threading activities were applied, there was a significant improvement, with the average score increasing to 84.06% in the second cycle. This research is expected to contribute to the development of more effective learning methods to enhance early childhood fine motor skills, as well as provide insights for educators and parents in supporting child development.